Rancang Bangun Game Edukasi Interaktif Berbasis Android untuk Mengenal Flora dan Fauna di Wilayah Paparan Sunda Berdasarkan Habitatnya - Destiani Siti Fatimah, Dini; Rengganis, Nadia (Jurnal Algoritma, 2025)
The Sunda Shelf is a region with high biodiversity in Indonesia. However, elementary school students' knowledge about this is still low due to the limited availability of interactive learning media. This study aims to develop an Android-based educational game to introduce flora and fauna based on their habitats. The method used is the Game Development Life Cycle (GDLC) with six stages: initiation, pre-production, production, testing, beta, and release. The game features four main habitats: tropical rainforest, swamp, mountains, and coast, equipped with visual materials and interactive quizzes. Testing was conducted through black-box and beta testing on 25 fifth-grade elementary school students. The results showed that 92% of respondents said the game was interesting and easy to use, and 88% felt it helped them understand the material. This game has proven to be an effective alternative learning medium that is interactive, fun, and supports early introduction to biodiversity.